EPC Agenda 2004-09-16 - Academic Senate:::::::::
Educational Policies Committee. Chair Report. Agenda – Approved. Minutes of 9/12/19 – Approved. Consent Item: Minimal Revision to EMBA program – Approved. President Report. Provost Report. Stevenson Hall Remodel Update. Vice President of Administrative and Finance Report. Vice President for Student Affairs Report. From EPC: Gerontology minor and certificate discontinuance – First Reading completed. From EPC: Discontinuance of Minor in Physical Science – discontinuance recommended. Graduate Studies Report. Associated Students Report. Statewide Senators Report. Revision to the Emeritus Policy – First Reading. Good of the Order.